A Study of the learners metaphorical perceptions of literary genres - Ekiz, Merve; Mutlu Kesen, Aynur (My University, 2016)
The perception of language has been studied from various aspects to date, whereas how students perceive literature remains today a less researched area. The quantity of qualitative research concerning the perception of literature needs to be increased. The present study aims to fill this gap by exploring students' perception in respect to the concept of literary genres through the use of metaphor as they reflect the way we perceive the world and shape our professional ideas and attitudes. In addition, the study investigates whether there is a difference in perceptions between junior and senior learners in regard to their perception of literary genres. The study participants were 58 first and 43 fourth grade ELL VWXGHQWV HQUROOHG LQ İVWDQEXO 8QLYHUVLW\ 7XUNHy. The data were collected through the use of semistructured interviews, multiple-choice questionnaire and metaphor elicitation papers. The metaphors of literary genres exhibited both the positive and negative perceptions of the learners. The Ring, Narnia,detergent concentrate, veritaserum ('iksir' in Turkish) and pomegranate were some of the unique positive metaphors of the learners. Some metaphors seem to be negative such as Pandora's Box, dark hole, ivy and labyrinth

Dilin algılanması ile ilgili farklı açılardan çalışmalar yapılmış olmasına rağmen edebiyatın algılanışı daha az araştırma yapılmış bir alandır. Bu nedenle edebiyatın algılanışı ile ilgili daha fazla niteliksel araştırmanın yapılması gerekmektedir. Bu çalışma, öğrencilerin edebi türler ile ilgili algılarını kullan-dıkları metaforik kavramlar ile araştırmayı amaçlamıştır. Çünkü metaforlar dünyayı algılama biçimimizi yansıtır ve profesyonel fikirlerimizi ve tutumlarımızı biçimlendirir. Ayrıca bu çalışma birinci sınıf ve dördüncü sınıf öğrencilerinin edebi türlere bakış açılarındaki farkı araştırmaktadır. Bu çalışmaya, İstanbul Üniversitesi İngiliz Dili ve Edebiyatı bölümü birinci sınıf öğrencilerinden 58, dördüncü sınıf öğrencilerinden 43 kişi katılmıştır. Çalışmanın verileri öğrencilerle yapılan görüşme, çoktan seçmeli anket ve metaforlarını yazmaları için hazırlanan form aracılığıyla elde edilmiştir. Edebi türler ile ilgili metaforlar, öğrencilerin olumlu ve olumsuz bakış açılarını yansıtmaktadır. Yüzük, Narnia, yoğunlaş-tırılmış deterjan, iksir ve nar öğrencilerin oluşturdukları özgün ve olumlu metaforlardan bir kısmıdır. Pandora'nın kutusu, kara delik, sarmaşık ve labirent gibi bazı metaforların olumsuz olduğu görülmektedir.
Öğrencilerin edebi türler ile ilgili metaforik algıları üzerine bir çalışma
Keywords: Perception of Literature; Literary Genres; Metaphorical Perceptions; Conceptual Metaphors; Edebiyatın Algılanışı; Edebi Türler; Metaforik Algılar; Kavramsal Metaforlar